Thrombus in transit after balloon atrial septostomy - Sakshi Sachdeva; Samir Shakya; Shyam Sunder Kothari (Wolters Kluwer Medknow Publications, 2020)
Deterioration following a successful balloon atrial septostomy (BAS) is not common. We report an unusual cause for the same. A thrombus in transit has not been previously reported following BAS.